2023
DOI: 10.1093/jac/dkad058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel carbapenem-hydrolysing class D β-lactamase RAD-1 inRiemerella anatipestifer

Abstract: Objectives To elucidate the role of a novel carbapenem-hydrolysing class D β-lactamase (RAD-1) from Riemerella anatipestifer. Methods We applied WGS and bioinformatic analysis to screen putative β-lactamase genes in R. anatipestifer SCVM0004. A putative class D β-lactamase gene was cloned into pET24a and transferred into Escherichia coli BL21 (DE3) for antibiotic susceptibility determination and protein purification. Meanwhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Through gene cloning, it was found that the mutant mediated resistance to penicillin, ampicillin, piperacillin, amoxicillin, cefotaxime, and cefazolin in β-lactam antibiotics in Escherichia coli . However, this gene did not exhibit high resistance in wild isolates, aligning with a previous study on tetX by Li et al (2022 ) , and the reported bla RAD-1 in R. anatipestifer ( Li et al, 2023 ). These observations suggest that while R. anatipestifer hosts to these resistance genes, they may manifest higher antibiotic resistance potential in other bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…Through gene cloning, it was found that the mutant mediated resistance to penicillin, ampicillin, piperacillin, amoxicillin, cefotaxime, and cefazolin in β-lactam antibiotics in Escherichia coli . However, this gene did not exhibit high resistance in wild isolates, aligning with a previous study on tetX by Li et al (2022 ) , and the reported bla RAD-1 in R. anatipestifer ( Li et al, 2023 ). These observations suggest that while R. anatipestifer hosts to these resistance genes, they may manifest higher antibiotic resistance potential in other bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…Table S3: List of strains whose rpoB gene sequences were used for comparative analysis and clustering. References [44][45][46][47][48][49][50][51][52]; Table S4: Primers used in this study for PCR detection of the resistance genes. References [31,32,[53][54][55][56][57][58][59].…”
Section: Detection Of Resistance Genesmentioning
confidence: 99%